The owners of new passenger vehicles: Some empirical findings on post-purchase patronage regarding servicing and repairs - C. Boshoff; P. J. Du Plessis (South African Journal of Business Management, 1989)
Despite concern among motor vehicle manufacturers about the relationship between their franchised dealers and new vehicle owners regarding servicing/repairs, very little empirical research has been done to investigate the post-purchase perceptions of new vehicle owners. Research studies conducted in America found that the expiry of the warranty on a new motor vehicle resulted in a major shift away from franchised dealers for servicing/repairs once the warranty had expired and that the older the vehicle became, the higher the probability that it would not be serviced by a franchised dealer. Information gathered from a random sample of new vehicle owners suggests that these conclusions also hold true for the South African situation, despite a high degree of satisfaction expressed with under-warranty servicing.
Keywords: 650